Magma and Mineral Composition Response to Increasing Slab-Derived Fluid Flux: Nevado de Longaví Volcano, Southern Chilean Andes - Sellés, Daniel; Dungan, Michael; Langmuir, Charles; Rodríguez, Ana Carolina; Leeman, William P. (Frontiers in Earth Science, 2022)
Nevado de Longaví volcano (NLV), in the Southern-Central Chilean Andes, has erupted during the Holocene magmas with compositions that are in several ways atypical for the region. These characteristics include elevated La/Yb ratios in evolved magmas, in an area of only moderately thick crust, coupled with low concentrations of K, Th, and other incompatible elements and elevated ratios of fluid-mobile (B, Cs, Li, Sb) to fluid-immobile elements. Samples have an unusual mafic mineralogy dominated by amphibole. The petrology of the Holocene products of NLV have been related to the influence of an oceanic transform fault (Mocha Fracture Zone; MFZ) that supplies the mantle wedge with unusually high amounts of fluids via dehydration of serpentinite bodies hosted by the subducted oceanic lithosphere. Because the trace of this transform fault is oblique to the convergence vector, its position along the arc has varied through time, as has the magnitude of its influence on the nature of the magmas erupted at NLV. The whole-rock and mineral chemistry of volcanic products from NLV, tied to a simplified stratigraphy, documents the secular changes in the magmatic system as the oceanic fault approached its current position. Magmas erupted ∼1–0.6 Ma are relatively low in water (as inferred from mineralogy and chemical proxies) and reduced (NNO-1 to NNO+0.5), and are similar to compositions found in neighboring volcanoes. From 0.25 Ma to the present, magmas are water-rich and oxidized (NNO-0.5 to NNO+1.7). In the intervening 0.6–0.25 Ma, mafic magmatism acquired a transient crustal component, which we identify as subducted sediment melts, on the basis of radiogenic isotopes and Pb, Th, and U abundances. Fluids released from serpentinite in the fracture zone were rich in Li, B, Sb, Cs and Ba, but not in K, Th, U and Sr. The fluid addition led to enhanced melting, particularly hydrous magmas that stabilized amphibole early during fractionation, higher oxygen fugacities, and distinctive chemical compositions.